Performance enhancement of PMSG systems with control of generator-side converter using d-axis stator current controller - K. Bunjongjit (2018)
This paper presents a performance enhancement of a permanent magnet synchronous generator (PMSG) system with control of generator-side converter for a wind turbine application. This method uses zero d-axis stator current control to minimize winding losses of the generator. The electromagnetic torque of the generator is correlated with the magnitude of the q-axis stator current, while the d-axis stator current is regulated at zero, the control scheme decouples dq-axis stator current control through vector control for the generator-side converter. This paper also presents mathematical analysis of the active power and stator power factor, and the maximum power point tracking (MPPT) operation. Simulation results are provided to guarantee the proposed control scheme, in which the performance enhancement and efficiency. © 2013 IEEE.